Establishing the reliability and validity of the diet culture beliefs scale - Hogan, Laura, author; Rickard, Kathryn, advisor; Conner, Bradley, committee member; Faw, Meara, committee member; Fisher, Gwenith, committee member (Colorado State University. Libraries, 2022)
Throughout history, human bodies have evolved to represent status, wealth, and morality through their shape and size. Although body objectification occurs across the gender spectrum, women have historically experienced the most pressure to fit whatever sociocultural norms are current. In recent decades, women whose bodies are thin and toned are often more highly valued in United States society than those who are in larger bodies. Efforts to transform and maintain the ideal body are rampant among women and include restrictive diets, excessive exercise, and pharmaceutical or surgical interventions. Dieting has become a pervasive part of United States culture. Research has shown that dieting is a strong predictor of eating disorders. Eating disorders account for more deaths than most mental illnesses, second only to opioid addiction. Eating disorders and disordered eating exist in people of all shapes and sizes, ethnic, and sociocultural backgrounds, but they often go undiagnosed because of the sociocultural stigma that only emaciated, young, wealthy, White women suffer from them. Early detection of eating disorders is crucial for successful treatment and intervention. This study explored the development of a new scale, the Diet Culture Beliefs Scale, by assessing its reliability and validity as a measure of individuals' internalized beliefs about the ways in which food and body size are indicative of morality and health. The goal of this study was to contribute a tool to both the body of research and clinical practice that may help medical and mental health providers identify warning signs of eating disorder development. Study results indicated that the Diet Culture Beliefs Scale retained its originally identified three-factor structure as evidenced by a Confirmatory Factor Analysis. Additionally, the Diet Culture Beliefs Scale showed both test- retest and internal consistency reliability, suggesting that it consistently measures diet culture beliefs over time and across items. Finally, the Diet Culture Beliefs Scale showed criterion- related, convergent, and discriminant validity suggesting that it is an accurate measure of diet culture as a unique construct. As such, the Diet Culture Beliefs Scale should be considered a psychometrically sound tool to support researchers and clinicians better understand the relationship between diet culture and eating disorders, as well as to provide early detection of eating disorder risk factors.
Keywords: diet culture; eating disorder; body image; exercise; disordered eating